3-Dimensional Ultrasound: How can the Fetal Corpus Callosum Be Demonstrated Correctly? - Pashaj, Sonila; Merz, Eberhard (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
The aim of this article is to outline the correct demonstration of the fetal corpus callosum with 3D ultrasound between 18 and 40 weeks of gestation. An abdominal or transvaginal 3D transducer can be used for acquisition of the fetal brain depending on the position of the fetus. The best demonstration of the corpus callosum can be achieved, when the volume with the corpus callosum is acquired from a sagittal or parasagittal sectional plane of the brain. Once the volume is stored in the memory, the multiplanar mode allows manipulation in all three dimensions until the exact median plane is seen, showing the corpus callosum as a hypo- or anechoic curved structure. Volume acquisition of the brain from an axial plane of the fetal head – typically used for biometrical measurements of the head diameters – is not recommended for clinical evaluation of the corpus callosum because the reconstructed median plane does not reveal the margins and the structure of the corpus callosum precisely. Other display modes such as volume contrast imaging (VCI), OmniView-VCI, and tomographic display may also be used for demonstration of the corpus callosum. However, these display modes only provide the operator with good image quality of the corpus callosum if the fetal brain was acquired from a sagittal and not from an axial plane.Conclusion 3D ultrasound is an excellent clinical tool for the exact presentation of the fetal corpus callosum because it allows volume manipulation of the fetal head in all three dimensions with precise demonstration of the median plane of the brain.
Keywords: fetus; corpus callosum; 3D ultrasound; how to